Inhibition of cellular HBV replication by bovine lactoferrin. - Lee, Benedict Jia Hong. (2010)
Hepatitis B virus (HBV) is a member of the Hepadnavirida family of virus and is composed of a circular genome of partially double stranded DNA. HBV causes the disease Hepatitis B which results in the transient or chronic infection of the liver. Lactoferrin is a iron-binding glycoprotein that is present in most biological fluids. They play an important role in mammals' innate immune system and are recognised as an effective anti-microbial peptide whose inhibition activities extends to other pathogens such as virus and fungi. They are believed to possess strong antiviral activities against Hepatitis C Virus and Hepatitis B virus. In this study, we had investigated the inhibitory effects of Bovine Lactoferrin on Hepatitis B viral replication in HBV infected HepG2.2.15 cells. MTT assay was first used to determine the cytotoxicity of Bovine Lactoferrin (BLf) with HepG2.2.15 cells for selection of suitable BLf treatment concentration to be used in our study. Reverse Transcription polymerase chain reaction (RT-PCR) was then used to quantify the HBV-DNA copies for comparing viral transcription activities between BLf treated cells and untreated control cells. BLf was found to be able to significantly inhibit the amplification of HBV-DNA in HBV-infected HepG2.2.15 cells in a dose dependent manner. The findings proposed that BLf could inhibit the HBV replication in cells by ingression into cells or through cell signalling via an integrated structure. In conclusion, our project has recommended BLf for consideration as a potential anti-HBV therapeutic reagent in the treatment of patients infected with Hepatitis B.